Appraisal analysis : attitude evaluation towards the three main characters in part III ' a thousand splended suns' novel - Salahuddin (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2020)
wt,1/irh,c.1